FACTORS AFFECTING INTENTION IN ACCOUNTING STUDY PROGRAM STUDENTS CHOOSING THE PUBLIC ACCOUNTANT PROFESSION - Dhian Rosalina; Kartika Yuliari; Warsani Purnamasari; Muhammad Rizqi Zati (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2020)
The research objective is to find out the factors that influence students' interest in choosing a Public Accountant career and dominant factors affect the perception of accounting students in choosing a career. Eighty accounting students at Samudra University, Langsa City were respondents in this study. The analytical technique used is Confirmatory Factor Analysis. The results of this study are the twelve items that affect student interest in career selection as a public accountant, formed into three main factors, namely 1) the intrinsic value factor of the job, 2) the professionalism factor, and 3) the labor market factor. Then, the three factors have an effect up to 77.3% on the selection of public accountant careers, while the rest are influenced by other factors outside this study. While the intrinsic value factor of a job has the highest eigenvalue score, which is 7.003 which means that the factor has the most dominant influence in the career selection of public accountants.